Experimental investigation on utilization of Sesbania grandiflora residues through thermochemical conversion process for the production of value added chemicals and biofuels - Janardhana, Kedri; Dhanalakshmi, C. Sowmya; Thilagham, K. T.; Chinnaiyan, Santhosh Kumar; Pillai, H. P. Jai Shanker; Sathish, T.; Agbulut, Umit; Palani, Kumaran; De Poures, Melvin Victor (NATURE PORTFOLIO, 2024)
All the countries in the world are now searching for renewable, environmentally friendly alternative fuels due to the shortage and environmental problems related with the usage of conventional fuels. The cultivation of cereal and noncereal crops through agricultural activities produces waste biomasses, which are being evaluated as renewable and viable fossil fuel substitutes. The thermochemical properties and thermal degradation behavior of Sesbania grandiflora residues were investigated for this work. A fluidized bed reactor was used for fast pyrolysis in order to produce pyrolysis oil, char and gas. Investigations were done to analyze the effect of operating parameters such as temperature (350-550 degrees C), particle size (0.5-2.0 mm), sweeping gas flow rate (1.5-2.25 m(3)/h). The maximum of pyrolysis oil (44.7 wt%), was obtained at 425 degrees C for 1.5 mm particle size at the sweep gas flow rate of 2.0 m(3)/h. Fourier transform infrared spectroscopy and gas chromatography-mass spectrometry methods were used to examine the composition of the pyrolysis oil. The pyrolysis oil is rich with aliphatic, aromatic, phenolic, and some acidic chemicals. The physical characteristics of pyrolysis oil showed higher heating value of 19.76 MJ/kg. The char and gaseous components were also analyzed to find its suitability as a fuel.
Keywords: Agricultural residues; Fast pyrolysis; Fluidized bed; Biofuel; Characterization; BIO-OIL PRODUCTION; PROCESS PARAMETERS; FLASH PYROLYSIS; RAPID PYROLYSIS; BED PYROLYSIS; BIOMASS; TEMPERATURE; FUEL; WOOD; Science & Technology - Other Topics